Ternary organic photodetectors based on pseudo-binaries nonfullerene-based acceptors. (29th June 2021) - Zhang, Tianyi; Moser, Maximilian; Scaccabarozzi, Alberto D; Bristow, Helen; Jacoutot, Polina; Wadsworth, Andrew; Anthopoulos, Thomas D; McCulloch, Iain; Gasparini, Nicola
Abstract: The addition of a third component to a donor:acceptor blend is a powerful tool to enhance the power conversion efficiency of organic solar cells. Featuring a similar operating mechanism, organic photodetectors are also expected to benefit from this approach. Here, we fabricated ternary organic photodetectors, based on a polymer donor and two nonfullerene acceptors, resulting in a low dark current of 0.42 nA cm −2 at −2 V and a broadband specific detectivity of 10 12 Jones. We found that exciton recombination in the binary blend is reduced in ternary devices due to the formation of a pseudo-binary microstructure with mixed donor–acceptor phases. With this approach a wide range of intermediate open-circuit voltages is accessible, without sacrificing light-to-current conversion. This results in ternary organic photodetector (TOPD) with improved Responsivity values in the near-infrared. Moreover, morphology analyses reveal that TOPD devices showed improved microstructure ordering and consequentially higher charge carrier mobilities compared to the reference devices.